Long-Term Warming Shifts the Composition of Bacterial Communities in the Phyllosphere of Galium album in a Permanent Grassland Field-Experiment - Aydogan, Ebru L.; Moser, Gerald; Müller, Christoph; Kämpfer, Peter; Glaeser, Stefanie P. (Frontiers in Microbiology, 2018)
Global warming is currently a much discussed topic with as yet largely unexplored consequences for agro-ecosystems. Little is known about the warming effect on the bacterial microbiota inhabiting the plant surface (phyllosphere), which can have a strong impact on plant growth and health, as well as on plant diseases and colonization by human pathogens. The aim of this study was to investigate the effect of moderate surface warming on the diversity and composition of the bacterial leaf microbiota of the herbaceous plant Galium album. Leaves were collected from four control and four surface warmed (+2°C) plots located at the field site of the Environmental Monitoring and Climate Impact Research Station Linden in Germany over a six year period. Warming had no effect on the concentration of total number of cells attached to the leaf surface as counted by Sybr Green I staining after detachment, but changes in the diversity and phylogenetic composition of the bacterial leaf microbiota analyzed by bacterial 16S rRNA gene Illumina amplicon sequencing were observed. The bacterial phyllosphere microbiota were dominated by Proteobacteria, Bacteroidetes, and Actinobacteria. Warming caused a significant higher relative abundance of members of the Gammaproteobacteria, Actinobacteria, and Firmicutes, and a lower relative abundance of members of the Alphaproteobacteria and Bacteroidetes. Plant beneficial bacteria like Sphingomonas spp. and Rhizobium spp. occurred in significantly lower relative abundance in leaf samples of warmed plots. In contrast, several members of the Enterobacteriaceae, especially Enterobacter and Erwinia, and other potential plant or human pathogenic genera such as Acinetobacter and insect-associated Buchnera and Wolbachia spp. occurred in higher relative abundances in the phyllosphere samples from warmed plots. This study showed for the first time the long-term impact of moderate (+2°C) surface warming on the phyllosphere microbiota on plants. A reduction of beneficial bacteria and an enhancement of potential pathogenic bacteria in the phyllosphere of plants may indicate that this aspect of the ecosystem which has been largely neglected up till now, can be a potential risk for pathogen transmission in agro-ecosystems in the near future.